القيادة التشاركية لرؤساء الأقسام وعلاقتها بالقيم التنظيمية: جامعة تبوك أنموذجا - آل قريشة، نجوى بنت علي بن محمد; الأحمدي، نسرين بنت عبدالحميد (جامعة تبوك, 2022)
هدفت الدراسة إلى التعرف على القيادة التشاركية لرؤساء الأقسام وعلاقتها بالقيم التنظيمية من وجهة نظر أعضاء هيئة التدريس بجامعة تبوك، اتبعت الدراسة المنهج الوصفي الارتباطي، وطبقت الاستبانة كأداة لجمع البيانات، وتكونت عينة الدراسة من (١٤٩) عضوا من أعضاء هيئة التدريس بكلية التربية والآداب وكلية إدارة الإعمال وكلية العلوم وكلية المجتمع بجامعة تبوك، وأظهرت نتائج الدراسة أن امتلاك سمات القيادة التشاركية لرؤساء الأقسام ككل جاءت بدرجة استجابة (محايد)، كما أن امتلاك رؤساء الأقسام لسمة العلاقات الإنسانية ولسمة المشاركة ولسمة تفويض السلطة جاءت بدرجة استجابة (محايد)، كما أن درجة توافر عناصر القيم التنظيمية لرؤساء الأقسام جاءت بدرجة (محايد)، وأن درجة توافر عنصر قيم إدارة الإدارة وعنصر قيم إدارة المهمة وعنصر قيم إدارة العلاقات الإنسانية وعنصر قيم إدارة البيئة لدى رؤساء الأقسام جاءت بدرجة استجابة (محايد)، كما أظهرت نتائج الدراسة وجود علاقة طردية قوية بين القيادة التشاركية ككل وبين كل من قيم إدارة الإدارة وقيم إدارة المهمة وقيم إدارة العلاقات الإنسانية وقيم إدارة البيئة والقيم التنظيمية ككل. بناء على نتائج البحث تم التوصل إلى تفعيل القيادة التشاركية داخل الأقسام من خلال عمل برامج ودورات ذات صلة مباشرة في تطوير مستوى الأداء لدى أعضاء هيئة التدريس، وإشراكهم في عملية تقييم الأداء وتوضيح نقاط القوة والضعف لديهم. This study aimed to identify the participatory leadership of departments’ heads from point of view of faculty members at Tabuk University, the study followed the relational descriptive methodology, the study employed a questionnaire as a data collection tool, the study sample included (149)members, Arts, Business Administration, Science Colleges, and Community College at Tabuk University, the study results showed that departments’ heads having participatory leadership features in total got (Neutral)response, departments’ heads having Human relationships feature in total got (Neutral)response, having participation feature was (Neutral), having authority delegation feature was (Neutral), availability degree of organizational values elements for departments’ heads was (Neutral), managerial values element was (Neutral), managerial values element was (Neutral), mission management values element was (Neutral), environment management values element was (Neutral). The results showed a significant positive relationship between the participatory leadership as a whole and managerial values, mission management values, human relations management values, environment management values, and organizational values as a whole. Important recommendations were: delegate faculty members some administrative skills, and to give them authorities to develop their leadership role; to engage faculty members in the process of performance evaluation and to clarify their strengths and weaknesses.
Keywords: السلوك التنظيمي -- القيادة التشاركية -- المبادئ التنظيمية -- المشاركة الجماعية -- العمل الجماعي